Subjective symptoms of RME patients treated with three different screw activation protocols: a randomised clinical trial - Halıcıoğlu Koray; Kiki Ali; Yavuz İbrahim (Sciendo, 2012)
Aims: The purpose of the present study was to evaluate the subjective symptoms of patients during the active phase of rapid maxillary expansion (RME) treatment, and further, to assess the differences between three different RME activation protocols.